Significance of 4P’s Government Program for the Beneficiaries in Selected HUMSS Students at Bestlink College of the Philippines: An Assessment: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Pantawid Pamilyang Pilipino Program, also known as 4Ps and formerly Bang on Pamilyang Pilipino, is the Philippine government's conditional cash transfer program under the Department of Social Welfare and Development. Pantawid Pamilyang Pilipino Program helps with financial assistance for the poorest Filipinos to improve their health and nutrition, especially the education of children aged up to 18 years old. It also helps a lot with daily food and debt repayment. This study aimed to determine the significance of the 4ps government program for the beneficiaries in selected HUMSS students at Bestlink College of the Philippines. This study will help the students know the problems or effects they encounter and also search for related literature and studies. Purposive sampling was also used to select the respondents of this study. Based on the answer, High Transportation expenses from cash-out remittance to students' addresses, School expenses due date not matching the date of release, and Students taking advantage of the 4p’s are mostly problems of the beneficiaries. The researcher concludes the effect of the 4ps on the academic performance of selected HUMSS students at Bestlink College of the Philippines.
Keywords: 4PS; Significance and Academic Performance